A 2D scintillator-based proton detector for high repetition rate experiments. (2019) - Huault, M.; De Luis, D.; Apiñaniz, J. I.; De Marco, M.; Salgado, C.; Gordillo, N.; Gutiérrez Neira, C.; Pérez-Hernández, J. A.; Fedosejevs, R.; Gatti, G.; Roso, L.; Volpe, L.
Abstract : We present a scintillator-based detector able to measure the proton energy and the spatial distribution with a relatively simple design. It has been designed and built at the Spanish Center for Pulsed Lasers (CLPU) in Salamanca and tested in the proton accelerator at the Centro de Micro-Análisis de Materiales (CMAM) in Madrid. The detector is capable of being set in the high repetition rate (HRR) mode and reproduces the performance of the radiochromic film detector. It represents a new class of online detectors for laser–plasma physics experiments in the newly emerging high power laser laboratories working at HRR.